Key indicators for Asia and the Pacific 2017 (Key Indicators for Asia and the Pacific Series, 2017)
Asia and the Pacific accounted for 40.9% of global GDP in 2016, up from 29.4% in 2000. The People's Republic of China, India, and Japan accounted for about 70% of the region's total output in 2016.